THE EFFECT OF ASSET STRUCTURE, CAPITAL STRUCTURE, MACRO ECONOMY AND FINANCIAL RISK MANAGEMENT ON THE VALUE OF THE FIRM IN COMPANIES LISTED ON THE JAKARTA ISLAMIC INDEX - solichah, solichah (Archives of Business Research, 2019)
The Islamic capital market has importtant roles, they are as a source of funding for companies for business development through the issuance of syari’ah securities, as a means of syari’ah securities for syari’ah capital market investors that are universal, can be utilized by anyone regardless of ethnic, religion and racial backgrounds. The purpose of this research to 1) examine, analyze and prove the Asset Structure, Capital Structure, Macroeconomics of Financial Risk Management, 2) examine, analyze and prove the Asset Structure, Capital Structure, Macroeconomics of the Value of the Firm, 3) examine, analyze and prove Financial Risk Management to the Value of the Firm. The population and sample in this study were 16 syri’ah stock companies listed on the Jakarta Islamic Index, from 2013 to 2017, with keriteria and saturated sampling techniques. This type of research is quantitative research secondary data research data obtained by IDX (Indonesia stock exchange) webset. Data examining techniques using PLS test equipment. The results show that the t-statistic: means: asset structure had no significant effect on financial risk management: means: asset structure had a significant effect on the value of the firm: means: capital structure has a significant effect on financial risk management: means: capital structure has no significant effect on the value of the firm: means: macro economic has a significant effect on financial risk management: giving the meaning of macro economic significantly influencing the value of the firm: giving the meaning of financial risk management having a significant effect on the value of the firm. Conclusions of the study 1) Asset structure has no effect and no significant effect on financial risk management, 2) Asset structure influences and significantly affects the value of the firm, 3) Capital structure influences and significantly affects financial risk management, 4) Capital structure has no effect and is insignificant on the value of the firm, 5) Macroeconomic influences and significantly on financial risk management, 6) Macroeconomics influential and significant on the value of the firm, 7) Financial risk management influences and significantly on the value of the firm